Suscetibilidade magnética e análise de incertezas em mapeamento de solos - Teixeira, Daniel De Bortoli [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The lack of information on spatial variability of soil attributes is one of the limiting factors for the development of different areas of knowledge and productive sectors. This information and the knowledge of their uncertainties allow the correct interpretation of results and possible decision making. The study was conducted in two stages: the first stage aimed to use geological, geomorphological, and pedological information in order to reduce the sampling density needed for the spatial characterization of magnetic susceptibility (MS), clay content and base saturation (BS); the second stage aimed to use the spatial uncertainty of MS and clay content for the delineation of mapping units. The study area, located in the municipality of Guatapará, has 870 ha and is characterized by geological transition Basalt - Alluvial Deposit - Eluvial-Colluvial Deposit, concave and convex landforms and presence of Oxisols and Entisols. 371 samples were collected at a depth of 0-0.25 m for the evaluation of MS, clay content and BS. The incorporation of secondary information in geostatistical models was performed through the simple kriging with varying local means. For MS, information about geology and geomorphology were responsible for approximately 45% and 44% of its spatial continuity. For clay content, these results were higher, indicating 54% (geology) and 53% (geomorphology). For BS, there was no relation between secondary information and its spatial continuity. The incorporation of geological and geomorphology information to the MS data allowed a reduction of 44% and 37% in the number of samples required to represent the spatial pattern of the attribute. For clay content was verified the possibility of reducing by 35% the number of samples using both information. In the second stage of the study, average and standard deviation (uncertainty) maps of MS and clay content were calculated based on 200 realizations of the sequential gaussian ...

A falta de informação sobre variabilidade espacial dos atributos dos solos é um dos fatores limitantes para o crescimento de diferentes áreas do conhecimento e setores produtivos. Estas informações aliadas ao conhecimento das suas incertezas possibilitam a correta interpretação dos resultados e possíveis tomadas de decisão aliadas a este. O estudo foi desenvolvido em duas etapas: na primeira etapa, objetivou-se, utilizar informações geológicas, geomorfológicas e pedológicas para a redução da densidade amostral necessária para a caracterização espacial da suscetibilidade magnética (SM), teor de argila e saturação por bases (V%); na segunda etapa objetivou-se, utilizar as incertezas espaciais da SM e teor de argila para o delineamento de unidades de mapeamento. A área de estudo, localizada no município de Guatapará, possui 870 ha e é caracterizada pela transição geológica Basalto - Depósito Aluvionar - Depósito Colúvio Eluvionar, formas da paisagem côncavas e convexas e presença de Latossolos e Neossolo. Foram coletadas 371 amostras na profundidade de 0-0,25 m para a avaliação da SM, teor de argila e V%. A incorporação das informações secundárias nos modelos geoestatísticos foi realizada por meio da krigagem simples com médias locais variando. Para a SM as informações sobre a geologia e geomorfologia foram responsáveis por cerca de 45% e 44% da sua continuidade espacial. Para o teor de argila, estes resultados foram superiores indicando 54% (geologia) e 53% (geomorfologia). Para o V%, não foi observada relação entre as informações secundárias e sua continuidade espacial. As incorporações das informações geológicas e geomorfológicas aos dados de SM propiciaram, respectivamente, a redução em 44% e 37% no número de amostras requeridas para representar o padrão espacial do atributo. Para o teor de argila foi verificada a possibilidade de redução em 35% no número de amostras...
Keywords: Cana-de-açúcar; Geologia - Métodos estatísticos; Mapeamento do solo; Susceptibilidade magnetica; Solos; Soil mapping